Musical Analysis. Historia - Theoria - Praxis, Vol. 7, 2025 - Granat-Janki, Anna. Redakcja (Akademia Muzyczna im. Karola Lipińskiego we Wrocławiu, 2025)
This is the seventh volume of the collective monograph devoted to music-analytical studies, the aim of which is to present musical analysis from historical, theoretical, and practical perspectives. The range of issues addressed is broad, as the authors – musicologists, music theorists, and composers from various academic centres in Poland and abroad (Austria, France, Germany, Lithuania, Serbia, Spain, and United Kingdom) – represent different research approaches, including semiotic, hermeneutic, axiological, and intertextual ones, and use different concepts and methods of analysing and interpreting a musical work in the search for sense and meaning in music. What draws attention is the wide application of analysis, including in the study of the relationship between music and the word, in the exploration of issues of genre, style, and compositional technique, as well as those of expression and narrative in music. The questions of performance and reception of music are also raised. We hope that the diverse discourses on music and different perspectives on musical analysis presented in this volume of Musical Analysis. Historia – Theoria – Praxis will prove insightful and interesting to readers.
Keywords: hermeneutics; intertextuality; word-music relations; genology; meaning in music